Sphere [videorecording (DVD)] - Wimmer, Kurt, 1964- (Warner Home Video, 2009)
"In the middle of the South Pacific, a thousand feet below the surface of the water, a huge vessel rests on the ocean floor. Rushed to the scene is a group of American scientists who descend to the depths of the sea to investigate this astonishing discovery. What they find defies their imaginations and mocks their attempts at logical explanation. It is a massive spaceship, undamaged from it's fall from the sky-and at least three hundred years old"--IMDb.